Нечистая сила: роман / Валентин Пикуль - Пикуль Валентин Саввич (Вече, 2000)
Экземпляры: ф.1 (2012) / Инвентарный номер: 54962 / Цена: 151.36 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 32 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44^VLBC/RL